Race-Specific and Skin of Color Dermatoscopic Characteristics of Skin Cancer: A Literature Review - Emmanouil Karampinis; Aimilios Lallas; Elizabeth Lazaridou; Enzo Errichetti; Zoe Apalla (Dermatology Practical & Conceptual, 2023)
Introduction: Individuals with melanin-rich skin account for the majority of the world's population. However, literature data regarding dermoscopic characteristics of skin cancer in skin of color (SoC) are scarce. The dermoscopic characteristics of cutaneous tumors might differ among skin types due to heterogeneity in composition and pigmentation.